Coral reefs and climate change in the Indian ocean: a case study of Watamu Marine National Park, Kenya and other Indian Ocean locations - Cowburn, B (2015)
Coral reefs are arguably the most threatened marine habitat because of multiple anthropogenic stressors degrading the health and resilience of these systems. In the past 20 years there have been increasing observations of mass coral bleaching and mortality associated with increasing water temperatures in the tropics. Reefs provide ecosystem services worth billions of dollars to people living in tropical coastal areas and are the architects of one of the most beautiful structures found on earth. Conserving these habitats is paramount, and conservation planning must contend with climate change along with local and regional stressors. In this thesis Watamu Marine National Park in Kenya is used as a case study of the current challenges facing the conservation of reefs in a warming world. The Western Indian Ocean suffered dramatic bleaching during 1998, which caused the mortality of 70% of Watamu's corals. Using datasets from the 1980s to present the historical trajectory of Watamu's reef community is presented. The current ecosystem resilience is assessed to suggest how this reef will respond to future climate stress. It appears that Watamu's coral community has remained in an altered state post-1998, which, based on its past thermal stress and current coral community, should be resistant to future bleaching. Watamu's resilience and reef health is compared with other locations in the Indian Ocean, including reefs in Kenya and the Maldives that bleached in 1998 and examples from Mozambique and Sumatra of reefs with little evidence of historical thermal stress. Resilience is a multi-faceted process with different major components and numerous interacting factors, which act synergistically on the reef community. Conservation options and opportunities are discussed for the 6 locations examined, using current resilience models and theory as a framework for identifying priority actions. Local and regional-scale human impacts on shallow marine habitats during the last 50 years has been dramatic, and with global-scale climate change as an additional major threat, the next 50 years will be critical for the future of reefs. The locations visited during this study showed encouraging signs of resilience to past thermal stress, with evidence to suggest that corals are acclimatising and/or adapting to increasing water temperatures. The future of reefs in locations like Watamu is uncertain. Better understanding of reef ecology, appropriate conservation techniques and ultimately greater public concern for reefs is required to ensure that there is a future for these ecosystems in the Indian Ocean.